Analisis Strategi Pemasaran Web Hosting PT Singcat Network - Liawatimena, Suryadiputra; Margono, Andy; Yati, Yati (Bina Nusantara University, 2006)
The development of business hosting in Indonesia is getting quicker and promising, along with the technology development and usage of internet. This development is followed by more companies that compete in hosting industry. Because of that, an analysis to one of the companies having hosting sector, PT Singcat Network was conducted. The result of analysis shows that company has a good strength to use available opportunity. But, until now the company is still less aggressive in market approaching. Strategy formulation that appropriate is needed to expand the market and in order to be able to compete and become the leader in hosting sector. Keywords: